From Followers to Buyers: The Impact of Influencer Vs Brand Advertising on Consumer Decisions (Journal of Asian Development Studies, 2025)
Social media is a revolution in the digital advertising industry, this is where a few ideas just cannot go wrong influencer marketing and brand advertising are plays that must not be looked down upon to achieve positive sales conversions. The purpose of this study is to examine through the lens of consumer perception of the informative value, entertainment value, trustworthiness, attractiveness, parasocial relationship, brand admiration, and persuasion knowledge of an influencer, and influencer-related factors that affect consumers' intention to purchase. The study builds upon source credibility theory, parasocial relationship theory, and the persuasion knowledge model, creating and testing a holistic conceptual framework that will be able to explain the conversion of social media followers to real buyers. The research design used was a quantitative, cross-sectional design with a structured questionnaire used to collect the data from the social media users. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results show that informative value (β = 0.367, p < 0.001) and entertainment value (β = 0.424, p < 0.001) significantly affect parasocial relationships, and trustworthiness (β = 0.153, p = 0.029) and attractiveness (β = 0.703, p < 0.001) significantly affect brand admiration. In addition, purchase intention (β = 0.714, p